IMPLEMENTASI KEBIJAKAN PENGADAAN BARANG DAN JASA E-PROCUREMENT PADA DINAS CIPTA KARYA, PERUMAHAN DAN TATA RUANG DAERAH PROVINSI SULAWESI TENGAH - Syarifuddin Syarifuddin (Katalogis, 2016)
This study aimed to analyze the process of implementation of the policy of procurement of goods and services e-procurement of Human Settlements, Public Housing Within Land Use Agency of Central Sulawesi province with reference to the theory of Implementation and George Edwards III, particularly four factors: (1) communication, (2 ) Resources, (3) Dispotition and (4) Structure of Bureaucracy. The research method used is qualitative method. Selection of informants as many as five people and were selected based on purposive sampling. The instrument is the researcher's own research and data collection through interviews, documentation and field observations. The results showed that in general the policy implementation process of procurement of goods and services e-procurement of Human Settlements, Public Housing Within Land Use Agency of Central Sulawesi Province have not found any indication of transparency. This is evident from the implementation of the process of procurement of goods and services. There are four (4) factors that support and hinder the implementation of the procurement of goods and services e-procurement of Human Settlements, Public Housing Within Land Use Agency of Central Sulawesi Province that is a factor of resources, communication, bureaucratic structure and other factors. Therefore, to cope with the indication of the required supervision of all parties so that it can run better without any suspicion.